2016
DOI: 10.1155/2016/4015271
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Left-Turn Driving Behavior at Signalized Intersections with Mixed Traffic Conditions

Abstract: In many developing countries, mixed traffic is the most common type of urban transportation; traffic of this type faces many major problems in traffic engineering, such as conflicts, inefficiency, and security issues. This paper focuses on the traffic engineering concerns on the driving behavior of left-turning vehicles caused by different degrees of pedestrian violations. The traffic characteristics of left-turning vehicles and pedestrians in the affected region at a signalized intersection were analyzed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…‘Following conflict’ driving behaviour was modelled to study the effect on flow, speed and other parameters of left moving traffic hindered by pedestrians [45]. In this model driving behaviour was converted into a mathematical expression which was taken into the simulation.…”
Section: Literature Review Of the Ca Model At The Intersectionmentioning
confidence: 99%
“…‘Following conflict’ driving behaviour was modelled to study the effect on flow, speed and other parameters of left moving traffic hindered by pedestrians [45]. In this model driving behaviour was converted into a mathematical expression which was taken into the simulation.…”
Section: Literature Review Of the Ca Model At The Intersectionmentioning
confidence: 99%
“…Furthermore, drivers who intend to turn left have to ensure that they do not interrupt crossing traffic. In the study of Li et al [2] left turning traffic in an intersection with an arrow traffic signal was analyzed. There it was shown that even when there is no other interaction (no pedestrians or crossing traffic) turning vehicles on average only drive at most v max,turner ≈ 40 km h ≈ 7 Cells time steps .…”
Section: Turning Rulesmentioning
confidence: 99%
“…Vehicular traffic in urban networks is known to be more complex than highway traffic because of additional influences like traffic lights, stopped vehicles, pedestrians or other influences [1][2][3]. The situation is further complicated by the possibility of vehicles not just to change lanes, accelerate or decelerate, but also turn directions at intersections.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…Given different traffic volumes, turning movement changes, and speed limits of the road links, the simulation results which can reflect the performance of signal optimization may be different. Li et al [40] modeled left-turn driving behavior to reveal the impact of different degrees of conflict on the performance of signal optimization under mixed traffic conditions. Considering the study in this paper is based on the assumption that traffic flow merely consists of single-motorized vehicle, the impact of degrees of conflict on signal optimization is neglected.…”
Section: Case Studymentioning
confidence: 99%